Democratizing Local Government with Political Parties: How do They Stand in Voters' Minds? - Tawakkal, George Towar Ikbal; Rahman, Ahmad Zaki Fadlur; Seitz, Thomas R; Garner, Andrew D (Universitas Muhammadiyah Malang, 2025)
A fundamental question about local government that is rarely explored by scholars is, what do voters think about the local elections? Scholars construct clear concepts of elections, but do these concepts resonate with the thoughts of voters? The importance of elections for voters can vary and have diverse consequences on their perceptions of elections, but the issue is that voters in many countries face numerous types of elections in their country. This diversity can impact the degree of importance and their perspectives on voting, including the position of political parties in the minds of voters. For example, in Indonesia, voters engage in eight types of elections including two local elections for a local government. This article questions the degree of importance voters attach to the local elections and their consequences for the position of political parties. The article is based on survey data from two regencies in Central Java, Indonesia, during 2019 with 800 respondents, as well as in-depth interviews with over 20 voters during 2023. The results indicate that the position of parties is jeopardized by the lack of data aligning with the importance of local election for voters. It indicates that voters do not see parties as main entities on local government.